Community Income Level from Swiftlet's Nest Business in Cempaka District, Banjarbaru City - Herliani, Herliani; Pahrurroji, Pahrurroji (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The complexity of managing a swiftlet nest business requires an in-depth analysis of the income levels of the community, especially in developing areas such as Cempaka District. This research aims to analyze the income levels of the community from the swiftlet nest business in Cempaka District, Banjarbaru City. The research was conducted in Cempaka District, Banjarbaru City. The sample consisted of five respondents who owned swiftlet nest buildings. Data analysis included building and installation costs, maintenance costs, labor costs, equipment costs, and other variable costs, as well as business revenue from the sale of swiftlet nests. The swiftlet nest business in Cempaka District, Banjarbaru City, provides a profitable income for the community. This is reflected in the net income earned, indicating that this business has good economic prospects and is able to improve the welfare of its owners. The income generated comes from efficient operational cost management and stable swiftlet nest prices in the market. Factors such as farming experience, building ownership, and management skills also contribute to the high income earned.